Categories of Documents on the State System of Standardization and Standardization in the Republic of Uzbekistan - Xaydarova Muxtasar Odiljon qizi; Berdaliyeva Moxlaroyim Abdulxamid qizi (Central Asian Journal of Theoretical and Applied Science, 2022)
This article provides information about the Standardization Service of the Republic of Uzbekistan, the State System of Standardization of the Republic of Uzbekistan, regulatory documents and categories on standardization.